2009
DOI: 10.1210/en.2009-0394
|View full text |Cite
|
Sign up to set email alerts
|

Chorionic Gonadotropin Regulates Prostaglandin E Synthase via a Phosphatidylinositol 3-Kinase-Extracellular Regulatory Kinase Pathway in a Human Endometrial Epithelial Cell Line: Implications for Endometrial Responses for Embryo Implantation

Abstract: Successful implantation necessitates modulation of the uterine environment by the embryo for a specific period of time during the menstrual cycle. Infusion of chorionic gonadotropin (CG) into the oviducts of baboons to mimic embryo transit induces a myriad of morphological, biochemical, and molecular changes in the endometrium. Endometrial epithelial cells from both baboons and humans when stimulated by CG in vitro, activates a cAMP-independent MAPK pathway leading to prostaglandin E(2) (PGE(2)) synthesis. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 71 publications
2
38
0
Order By: Relevance
“…Moreover, a recent study showed that the human embryonic signal, chorionic gonadotropin, regulates the mPGES-1 promoter and induces mPGES-1 synthesis in endometrial epithelial cells via the PI3K-ERK1/2 pathway (Banerjee et al 2009). Interestingly, in rats, mPGES-1 mRNA and protein were only detected in the subluminal stroma surrounding the implanting blastocyst at the implantation site on day 6 of pregnancy, but were not observed in the inter-implantation site on day 6 of pregnancy and on day 6 of pseudopregnancy (Cong et al 2006).…”
Section: Some New Insights On Pg Synthesis During Early Pregnancy Inmentioning
confidence: 99%
“…Moreover, a recent study showed that the human embryonic signal, chorionic gonadotropin, regulates the mPGES-1 promoter and induces mPGES-1 synthesis in endometrial epithelial cells via the PI3K-ERK1/2 pathway (Banerjee et al 2009). Interestingly, in rats, mPGES-1 mRNA and protein were only detected in the subluminal stroma surrounding the implanting blastocyst at the implantation site on day 6 of pregnancy, but were not observed in the inter-implantation site on day 6 of pregnancy and on day 6 of pseudopregnancy (Cong et al 2006).…”
Section: Some New Insights On Pg Synthesis During Early Pregnancy Inmentioning
confidence: 99%
“…30,31 The HES cells were cultured, passaged, and maintained in phenol red-free, high glucose Dulbecco Modified Eagle Medium (Invitrogen, Carlsbad, California) supplemented with 10% FBS (Atlanta Biologicals) and 120 U/mL penicillin/streptomycin (Cambrex). Once cells reached confluency, they were transferred to serum-free medium containing only antibiotics for 24 hours and then conditioned medium (CM) was collected.…”
Section: Cell Isolation Culture and Treatmentsmentioning
confidence: 99%
“…Prostaglandin E2 (PGE2) induces cAMP in endometrial stromal cells to promote their predecidualization response during the secretory phase (Tanaka et al 1993). According to results from our and other laboratories, treatment of both human and baboon endometrial epithelial cells with CG induces expression of cyclooxigenase-2 (COX2, coded by PTGS2 ) and prostaglandin E synthase (PGES), two enzymes that control the synthesis of PGE2 (Banerjee et al 2009; Zhou et al 1999), as well as the production of PGE2 (Srisuparp et al 2003). The response of endometrial epithelial cells to CG and the downstream PGE2 production occurs through the CG receptor LHCGR, a seven transmembrane G protein-coupled receptor, and the inositol phosphate-dependent mitogen-activated protein kinases (MAPK) pathway (Banerjee et al 2009).…”
Section: Endometrial Response To Blastocyst/conceptus Signalsmentioning
confidence: 99%
“…According to results from our and other laboratories, treatment of both human and baboon endometrial epithelial cells with CG induces expression of cyclooxigenase-2 (COX2, coded by PTGS2 ) and prostaglandin E synthase (PGES), two enzymes that control the synthesis of PGE2 (Banerjee et al 2009; Zhou et al 1999), as well as the production of PGE2 (Srisuparp et al 2003). The response of endometrial epithelial cells to CG and the downstream PGE2 production occurs through the CG receptor LHCGR, a seven transmembrane G protein-coupled receptor, and the inositol phosphate-dependent mitogen-activated protein kinases (MAPK) pathway (Banerjee et al 2009). Interestingly, treatment with CG failed to induce production of cAMP in endometrial epithelial cells, but leads to a release of PGE2 which induces cAMP production in stromal cells (Srisuparp et al 2003; Tanaka et al 1993), suggesting the role of epithelial cells mediating the stromal response to embryonic CG.…”
Section: Endometrial Response To Blastocyst/conceptus Signalsmentioning
confidence: 99%